Developing Physical Education and Recreation Module for Students in Faculty of Teacher Training and Education at Universitas Bung Hatta - Meiriani Armen; Apriyanti Rahmalia (Journal Physical Education, Health and Recreation, 2020)
This study aims to produce a valid learning module for Swimming subjects. This type of research is research and development (R & D). This study looks at whether the module designed is valid, then an expert trial is conducted, namely the Learning expert in swimming. Aspects tested were tested to experts, namely Material Aspects in Modules, Presentation Aspects in Modules and Aspects of Language and Readability. The Try Out subjects were students of the Physical Health and Recreation Education study program who had taken swimming courses. The module research results based on three aspects of the assessment obtained an average value of 3.98 and categorized as valid or useful. In the solid phase or student trials, the module is classified as very practical.